The Symbol of the Unconquered - A Story of the Ku Klux Klan - Roach, Max (bfi, 2016)
The critic J. Hoberman has described Micheaux as the "Black Pioneer of American film - not just because he was a black man, or because in his youth he pioneered the West, or because he was the greatest figure in 'race' movies and an unjustly ignored force in early American cinema. Micheaux is America's Black Pioneer in the way that André Breton was Surealism's Black Pope. His movies throw our history and movies into an alien and startling disarray." One of Micheaux's earliest surviving films, "The Symbol of the Unconquered" is a stirring melodrama about the westward migration of a young African American woman from her native Selma, Alabama, to the Pacific Northwest town of Orison. Micheaux provided a dramatic rebuttal to the racism of D. W. Griffith's "Birth of a Nation": as one advertisement for the film read, "See the Ku Klux Clan in action - and their annihilation". [www.moma.org]